Contemplation and salvation in the Eleusinian mysteries - Masís Iverson, Katherine (2026)
This paper describes the manner in which the Eleusinian mysteries propitiated soteria or salvationand epopteia or contemplation among their initiates. Mystery cults are cosmopolitan rather than local, andindividually rather than collectively oriented. The Eleusinian mysteries seemed to offer life-transformingpractices and rituals to their initiates.